Metagenomic insights to bacterial communities, functional traits, and soil health in banana smallholder agroecosystems of Kenya - Muzami, Eugene Mwanza; Kitundu, George; Muriithi, Oscar Mwaura; Kavoo, Agnes Mumo; Gichuru, Virginia Gathoni; Mbinda, Wilton Mwema (Frontiers in Microbiology, 2025)
Microbes inhabiting the banana rhizosphere are varied and mediate essential functions that enhance plant growth and increase crop productivity. Their abundance in soil habitats is a potential indicator of soil health and quality. Despite the well-known benefits of rhizosphere microorganisms in banana cultivation, their genomic and functional diversity remains largely unexplored within smallholder agroecosystems. In this study, we characterized the community composition and functional potential of bacteria in banana rhizospheric soils from Gituamba, Mangu and Ngenda constituencies in Kiambu County, Kenya. Using Illumina Novaseq sequencing, we analyzed 16S rRNA gene amplicons and shotgun metagenomic profiles to explore these microbial communities. Variations of soil physicochemical parameters across the study sites were assessed. The parameters varied across the sites, with soils in Gituamba and Ngenda depicting better soil fertility characteristics than Mangu. Amplicon sequencing profiles revealed higher bacterial diversity in Gituamba compared to Mangu, while the single sample from Ngenda exhibited moderate diversity. The dominant phyla across the study sites were Proteobacteria, Actinobacteria, and Cyanobacteria. Functional profiling of 16S rRNA gene amplicons showed a higher enrichment in Gituamba compared to Mangu. Overall, the functional profiling indicated that predicted metabolic pathways across the study sites were linked to genes encoded by the members of the most abundant bacterial phyla in the soil environments, majorly contributing to beneficial roles for soil health and crop yield. This study offers methods to reveal the banana rhizosphere as a rich reservoir for potential microbes of agricultural and biotechnological significance, which can promote sustainable agriculture.